Rituximab Biosimilar Prevents Poor Outcomes of Microscopic Polyangiitis and Granulomatosis with Polyangiitis as Effectively as Rituximab Originator - Kwon, Hyeok Chan; Kim, Minyoung Kevin; Song, Jason Jungsik; Park, Yong-Beom; Lee, Sang-Won (Yonsei medical journal, 2020)
There has been no extensive study to compare the efficacy between rituximab originator (Mabthera®) and its biosimilar (Truxima®) for microscopic polyangiitis (MPA) and granulomatosis with polyangiitis (GPA). Here, we investigated the clinical effects of rituximab on poor outcomes of MPA and GPA in Korean patients, and compared those between Mabthera® and Truxima®.PURPOSEThere has been no extensive study to compare the efficacy between rituximab originator (Mabthera®) and its biosimilar (Truxima®) for microscopic polyangiitis (MPA) and granulomatosis with polyangiitis (GPA). Here, we investigated the clinical effects of rituximab on poor outcomes of MPA and GPA in Korean patients, and compared those between Mabthera® and Truxima®.We retrospectively reviewed the medical records of a total of 139 patients, including 97 MPA patients and 42 GPA patients. At diagnosis, antineutrophil cytoplasmic antibody positivity and comorbidities were assessed. During follow-up, all-cause mortality, relapse, end-stage renal disease, cerebrovascular accident and acute coronary syndrome were evaluated as poor outcomes. In this study, rituximab was used as either Mabthera® or Truxima®.MATERIALS AND METHODSWe retrospectively reviewed the medical records of a total of 139 patients, including 97 MPA patients and 42 GPA patients. At diagnosis, antineutrophil cytoplasmic antibody positivity and comorbidities were assessed. During follow-up, all-cause mortality, relapse, end-stage renal disease, cerebrovascular accident and acute coronary syndrome were evaluated as poor outcomes. In this study, rituximab was used as either Mabthera® or Truxima®.The median age at diagnosis was 60.1 years and 46 patients were men (97 MPA and 42 GPA patients). Among poor outcomes, patients receiving rituximab exhibited a significantly lower cumulative relapse-free survival rate compared to those not receiving rituximab (p=0.002). Nevertheless, rituximab use did not make any difference in other poor outcomes of MPA and GPA except for relapse, which might be a rebuttal to the fact that rituximab use after relapse eventually led to better prognosis. There were no significant differences in variables at diagnosis and during follow-up between patients receiving Mabthera® and those receiving Truxima®. Patients receiving Truxima® exhibited a similar pattern of the cumulative survival rates of each poor outcome to those receiving Mabthera®.RESULTSThe median age at diagnosis was 60.1 years and 46 patients were men (97 MPA and 42 GPA patients). Among poor outcomes, patients receiving rituximab exhibited a significantly lower cumulative relapse-free survival rate compared to those not receiving rituximab (p=0.002). Nevertheless, rituximab use did not make any difference in other poor outcomes of MPA and GPA except for relapse, which might be a rebuttal to the fact that rituximab use after relapse eventually led to better prognosis. There were no significant differences in variables at diagnosis and during follow-up between patients receiving Mabthera® and those receiving Truxima®. Patients receiving Truxima® exhibited a similar pattern of the cumulative survival rates of each poor outcome to those receiving Mabthera®.Truxima® prevents poor outcomes of MPA and GPA as effectively as does Mabthera®.CONCLUSIONTruxima® prevents poor outcomes of MPA and GPA as effectively as does Mabthera®.